The Trail West: Hang Him Twice - Book 2 - Johnstone, William W.; Johnstone, J. A. (New York, NY : Pinnacle Books, 2018)
Accidental outlaw Dooley Monahan unexpectedly finds himself first the owner of a silver mine in the lawless boomtown of Leadville, Colorado, and then the towns marshal, which forces him into the crossfire between two rival gangs.
Keywords: Monahan, Dooley (Fictitious character) -- Fiction; Sheriffs -- Fiction; Gangs -- Fiction; Frontier and pioneer life -- West (U.S.); Fiction; Leadville (Colo.); Fiction; Western fiction